Pengaruh Struktur Kepemilikan, Keputusan Investasi, Dan Keputusan Pendanaan Terhadap Nilai Perusahaan (Kasus pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2013-2015) - Karima, Selvia Yuliane, Dra. Wuryaningsih DL, MM (2017)
This study aims to determine the effect of ownership structure that includes Managerial Ownership, Institutional Ownership, Investment Decisions and Financing Decisions on Corporate Values in companies listed on the Indonesian Stock Exchange (BEI) chemical and basic industry sectors. Welfare for shareholders and increase the value of the company are related, for the welfare of shareholders on condition that enhance shareholder value through share price. The higher the stock price, the higher the wealth of shareholders, it is also further enhance shareholder value. The data used are secondary data. Mechanical sampling using purposive sampling of 60 companies base and chemical industry listed in Indonesia Stock Exchange acquired 28 companies that match the criteria. Analysis of the data is quantitative data collection techniques documentation method. The results showed the results of the t test variable Managerial Ownership and Investment Decisions have an impact on company value. while variable Institutional Ownership and Financing Decision has no influence on company value. F test results showed variable Manajerila Ownership, Institutional Ownership, Investment Decisions and Financing Decisions have simultaneous effect on the Company Values. Company value can be explained by the variable Managerial Ownership, Institutional Ownership, Investment Decisions and Financing Decisions of 41.5% and the remaining 58.5% is explained by other variables outside the study.